Evaluation of the peritoneal carcinomatosis index with CT and MRI. Issue 9 (4th April 2017) - Dohan, A; Hoeffel, C; Soyer, P; Jannot, A S; Valette, P-J; Thivolet, A; Passot, G; Glehen, O; Rousset, P
Abstract: Background: The aim was to determine the incremental value of MRI compared with CT in the preoperative estimation of the peritoneal carcinomatosis index (PCI). Methods: CT and MRI examinations of patients with peritoneal carcinomatosis were evaluated. CT images were first analysed by two observers who determined a first PCI (PCICT ). Then, the two observers reviewed MRI examinations in combination with CT and determined a second PCI (PCICT + MRI ). The sensitivity and negative predictive value of the two imaging sets were determined using surgery as a reference standard (PCIRef ). Results: CT plus MRI was more accurate in predicting the surgical PCI than CT alone. The absolute difference between PCICT + MRI and PCIRef was lower than that between PCICT and PCIRef (mean(s.d.) 3·96(4·10) versus 4·89(4·73); P = 0·010). The number of true-positive findings increased from 106 to 125 for reader 1 and from 117 to 132 for reader 2 with the adjunct of MRI. For both readers, an increased sensitivity was obtained when both MRI and CT were used (from 63 to 81 per cent for reader 1; from 44 to 81 per cent for reader 2). The increase in sensitivity was greater for patients with a moderate volume of disease. Conclusion: The combination of CT and MRI improved the preoperative estimation of PCI compared with CT alone. Abstract : Combination useful